Sinfonia: Cross-tier orchestration for edge-native applications - Satyanarayanan, Mahadev; Harkes, Jan; Blakley, Jim; Meunier, Marc; Mohandoss, Govindarajan; Friedt, Kiel; Thulasi, Arun; Saxena, Pranav; Barritt, Brian (Frontiers in the Internet of Things, 2022)
The convergence of 5G wireless networks and edge computing enables new edge-native applications that are simultaneously bandwidth-hungry, latency-sensitive, and compute-intensive. Examples include deeply immersive augmented reality, wearable cognitive assistance, privacy-preserving video analytics, edge-triggered serendipity, and autonomous swarms of featherweight drones. Such edge-native applications require network-aware and load-aware orchestration of resources across the cloud (Tier-1), cloudlets (Tier-2), and device (Tier-3). This paper describes the architecture of Sinfonia, an open-source system for such cross-tier orchestration. Key attributes of Sinfonia include: 1. Support for multiple vendor-specific Tier-1 roots of orchestration, providing end-to-end runtime control that spans technical and non-technical criteria; 2. Use of third-party Kubernetes clusters as cloudlets, with unified treatment of telco-managed, hyperconverged, and just-in-time variants of cloudlets; 3. Masking of orchestration complexity from applications, thus lowering the barrier to creation of new edge-native applications. We describe an initial release of Sinfonia (https://github.com/cmusatyalab/sinfonia), and share our thoughts on evolving it in the future.